Fatigue Crack Growth Analysis On Square Prismatic With Embedded Cracks Under Tension Loading - M. S., Shaari; A. K., Ariffin; Takahashi, Akiyuki; S., Abdullah; Kikuchi, Masanori; M. R. M., Akramin (Faculty Mechanical Engineering, UMP, 2017)
One of the most important issues yet to be overcome by engineers is the integrity and reliability of engineering structures. This is to ensure the safety of the engineering structure is at the greatest since the catastrophic failures usually occur due to fatigue crack growth. Due to insufficient studies on the fatigue embedded crack growth, the prismatic bar is chosen as the model of the structure. It is wise to select the solid bar since the analysis can be much simpler, thus making it easier to examine the behaviour of the fatigue crack growth. In this study, the metallic square prismatic with embedded cracks is analysed using S-version Finite Element Modelling (S-version FEM) under tension loading. The S-version FEM is an open source program, that is built from codes previously compiled as a program. The S-version FEM structured using the global-local overlay technique consists of two separate global and local meshes. By using the basic concept from the energy release rate and stress intensity factors (SIF), the behaviour of the fatigue crack growth is analysed. From the linear elastic fracture mechanics concept, the SIF is calculated using the virtual crack closure-integral method. The influences of different initial crack size and aspect ratios on the fatigue crack growth are investigated in this study. In addition, the SIF results from the S-version FEM are compared with the analytical solutions. From the analysis, the root mean square errors (RMSE) are performed to support the validation. The RMSE shows a very small error of 0.227, 0.086 and 0.3089 according to the aspect ratio of 0.5, 1.0 and 2.0, respectively. The results also show significant characteristics and behaviour of the SIF trend along the crack front, corresponding to different aspect ratios. From this study, the S-version FEM is suitable to be used to predict the fatigue crack growth for the cracks embedded in a structure. Subsequently, the S-version FEM is an open source program can be modified for increasingly complex engineering problems.